Analisis Faktor-Faktor Yang Mempengaruhi Akuntabilitas &Transparansi Informasi Keuangan Daerah Melalui Website - Indra Agung Wilopo (Universitas Alma Ata, 2017)
Abstracts : This research aims to find new evidence, the factors that affect the accountability and transparency of financial information via the website area. With the rules and regulations related to the disclosure of public information, as the practice of good governance, all government units are obliged to submit financial information to the public in a transparent manner. One media delivery of such information is through the website. Based on a review of literature and previous research, we use the seven factors suspected to affect the accountabilitty and transparency of financial information via the website area, the factors are the ratio of PAD, the size of the local government, the complexity of the administration, the ratio of debt financing, shopping areas, the level of welfare and quality of financial reporting area. In this study, researchers used the several districts government and cities in Indonesia, and run two test models are logistic regression and multiple linear regression. The results showed that the only factor which the level of welfare significant positive effect on the transparency of financial information via the website regions, whereas other factors had no significant effect. This indicates that the public welfare, which implies the use of Internet media to access the area of financial information. These results imply that the presentation of financial information based pressure area information needs of the community have access to the internet, that people who are already good level of welfare.